Stomach frame-count-based attenuation correction of dynamic posterior view gastric emptying scintigraphy with continuous acquisition in children - Cao, Xinhua (Pediatr Radiol, 2017)
BACKGROUND: When performing dynamic gastric emptying scintigraphy with continuous acquisition in children, a single posterior view acquisition is preferred because it allows the young patient to more easily interact with a parent or technologist even though this method tends toward overestimating gastric emptying. OBJECTIVES: The objective of our study was to develop a new attenuation correction (AC) method to improve the accuracy of the time activity curve and the measurement of residual gastric emptying from 1-h posterior images of gastric emptying scintigraphy with continuous acquisition. MATERIALS AND METHODS: We developed a frame-count-based AC for gastric emptying scintigraphy from the posterior view (posterior AC method). We retrospectively reviewed 122 gastric emptying studies performed in children using conjugated posterior and anterior views, and evaluated the statistical differences between posterior only (without AC) and posterior AC using the geometric mean method as a reference standard. RESULTS: The residual values obtained using posterior AC were not significantly different (P=0.813) compared to those using the geometric mean while the values using the posterior only were significantly different (P<0.001) from the geometric mean. CONCLUSION: The proposed method can replace the geometric mean method to estimate gastric emptying residual fraction using patient-friendly posterior view without a significant difference in 1-h gastric emptying scintigraphy with continuous acquisition.